No solidarity without liberty. Why is it so tricky to comprehend solidarity as a political ideal? - Boursier, Tristan (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2020)
It seems complicated for contemporary literature in political science to use the concept of solidarity with a normative intention at the state level. If the concept experienced a boom in Europe at the end of the 19th century, it is supplanted today by other terms such as justice or the welfare state. In this article, I explore the following hypothesis: it is difficult to use the concept of solidarity because it conflicts with individual liberty, which is the cause of a specifically liberal caution concerning this concept. Contemporary liberal thinkers would prefer to ignore solidarity as a value because it has several characteristics that cause tension. I will mainly dwell on the binding dimension of solidarity and its relation to the centrality of individual liberty in liberalism.